Frailty and dementia risks in asymptomatic cerebral small vessel disease: A longitudinal cohort study. (September 2022) - Chung, Chih-Ping; Lee, Wei-Ju; Chou, Kun-Hsien; Lee, Pei-Lin; Peng, Li-Ning; Wang, Pei-Ning; Lin, Ching-Po; Chen, Liang-Kung
Highlights: A potential predictor of dementia conversion in cerebral small vessel disease (CSVD). CSVD people with mobility frailty had higher risk of dementia at 5.7 years. Mobility frailty may serve as one clinical marker for adverse outcomes of CSVD. Mobility frailty might be involved in the mechanism of cognitive declines in CSVD Abstract: Objectives: Frailty has been shown to predict adverse outcomes in several diseases. We aimed to evaluate the associations between frailty profiles, both severity and subtype, and dementia risk in a community-based population with asymptomatic (without stroke and dementia) cerebral small vessel disease (CSVD). Methods: Individuals with asymptomatic CSVD were recruited from the community-based I-Lan Longitudinal Aging Study between 2011 and 2014 (baseline) and were followed up between 2018 and 2019. All participants underwent CSVD assessment by 3T brain MRI, as well as physical and cognitive assessments at baseline. Univariate and multivariate logistic regression analyses were performed to evaluate the associations between each factor and dementia conversion at follow-up. Results: Among 261 participants with asymptomatic CSVD (64.8 [50.0-89.1, 8.4] years; 136 [52.1%] men), 13 (5.0%) developed dementia during a mean follow-up of 5.7 (0.7) years. Dementia converters were less likely to be robust (30.8% vs. 61.5%) and more likely to be pre-frail/frail (69.2% vs. 38.5%) than non-converters ( p = 0.040). Meanwhile, there was significantly more frequent mobility frailty (53.8% vs. 19.8%, p = 0.009), but a similar prevalence of non-mobility frailty in dementia converters compared with non-converters. Univariate analyses showed that neither frailty severity nor CSVD burden was associated with a higher risk of dementia; it was the frailty subtype, the mobility frailty, which was significantly associated with dementia conversion in participants with asymptomatic CSVD, with an odds-ratio of 4.8 (95% CI = 1.5–14.8, p = 0.007). The significance remained after adjusting for age, sex, education and baseline cognitive function, respectively. Conclusion: Mobility frailty was associated with a higher risk of incident dementia in individuals with subclinical CSVD. Mobility frailty might be involved in the pathology of cognitive decline in CSVD and potentially serve as a marker to identify people at risk of cognitive impairment at an early stage of CSVD.